2010
DOI: 10.1039/c003836a
|View full text |Cite
|
Sign up to set email alerts
|

The synchronization of superparamagnetic beads driven by a micro-magnetic ratchet

Abstract: We present theoretical, numerical, and experimental analyses on the non-linear dynamic behavior of superparamagnetic beads exposed to a periodic array of micro-magnets and an external rotating field. The agreement between theoretical and experimental results revealed that non-linear magnetic forcing dynamics are responsible for transitions between phase-locked orbits, sub-harmonic orbits, and closed orbits, representing different mobility regimes of colloidal beads. These results suggest that the non-linear be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“…When the rotational frequency of the external field becomes too high for a bead to follow, it starts to move with V < 1 before becoming stationary (V ¼ 0). 16 Thus, there is a maximum and critical frequency, f V ¼ 1 , up to which a bead can follow the traveling magnetic wave with phase-locked velocity. The corresponding maximum magnetic bead velocity is…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…When the rotational frequency of the external field becomes too high for a bead to follow, it starts to move with V < 1 before becoming stationary (V ¼ 0). 16 Thus, there is a maximum and critical frequency, f V ¼ 1 , up to which a bead can follow the traveling magnetic wave with phase-locked velocity. The corresponding maximum magnetic bead velocity is…”
Section: (B)mentioning
confidence: 99%
“…[12][13][14] Moreover, arrays of cobalt micro-magnets in combination with a rotating external magnetic field have been used for the magnetophoretic transportation of magnetic beads, and their ability to separate beads with different magnetophoretic mobilities by tuning the frequency of the applied magnetic field has been demonstrated. [15][16][17] Previously, we have shown that magnetic beads can be selectively transported between stripes on a chip with periodic arrays of long exchange-biased permalloy microstripes using a rotating external magnetic field. 18 Recently, the use of a continuous film with a periodic array of exchange-biased stripes with alternating magnetization orientations induced by ion bombardment was also presented.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetically actuated microrobots appear to be the most promising because of this method is minimally invasive to a cell, features a noncontact drive, and has a low production cost [9][10][11][12][13]. Nelson et al controlled the untethered microrobots using electromagnetic fields [14].…”
Section: Introductionmentioning
confidence: 99%
“…The desired capabilities of single-cell arrays bear strong resemblance to random access memory (RAM) computer chips, including the ability to introduce and retrieve single cells from precise locations of the chip (writing data), and query the biological state of specified cells at future time points (reading data). Existing particle handling tools based on hydrodynamic 8-11 , optic 12-18 , electric [19][20][21][22] and magnetic [23][24][25][26][27][28][29][30][31][32][33][34][35][36] trapping forces can achieve parts of this desired functionality; however, no single technique to our knowledge encompasses the scalability, flexibility and automation that allows single-cell chips to perform with the level of integration of computer circuits.Our approach has significant similarities with magnetic bubble memory technology 37 , which was originally developed to store memory and implement logic through the precise manipulation of 'magnetization bubbles' in iron garnet films. Previous works demonstrated that magnetization bubbles could be moved along specific tracks and into desired storage locations by controlling the electrical and magnetic circuitry patterned on top of the garnet films.…”
mentioning
confidence: 99%
“…The desired capabilities of single-cell arrays bear strong resemblance to random access memory (RAM) computer chips, including the ability to introduce and retrieve single cells from precise locations of the chip (writing data), and query the biological state of specified cells at future time points (reading data). Existing particle handling tools based on hydrodynamic [8][9][10][11] , optic [12][13][14][15][16][17][18] , electric [19][20][21][22] and magnetic [23][24][25][26][27][28][29][30][31][32][33][34][35][36] trapping forces can achieve parts of this desired functionality; however, no single technique to our knowledge encompasses the scalability, flexibility and automation that allows single-cell chips to perform with the level of integration of computer circuits.…”
mentioning
confidence: 99%